Enhancing computational efforts with consideration of probabilistic available transfer capability using probabilistic collocation method - Khairuddin, Azhar; Khalifa, Othman Omran; Alhammi, Abdelwahab I. (Universiti Teknologi Malaysia, 2016)
Most of Probabilistic Load Flow (PLF) studies with consideration of generation and load uncertainties concern with reducing efforts computational in addition high accuracy. One of the most famous expansion method used is Gram-Charlier and Comulants. This paper proposed a Probabilistic Collocation Method (PCM) to improve the common used PLF computation methods in order to model the network topology uncertainties. This method uses Probabilistic Distribution Functions (PDF) concept to model the impact of network uncertainties as a linear function of power injections. Maintaining the linear relationship between line flows and power injections of transmission line flows. The proposed method is examined using IEEE39-bus test system. Numerical comparison with Monte Carlo simulation method was presented in this paper. Study results indicated that the proposed method has significantly reduced the computational efforts while maintaining a high degree of accuracy.